Photocatalytic Micromotors Activated by UV to Visible Light for Environmental Remediation, Micropumps, Reversible Assembly, Transportation, and Biomimicry - Kong, Lei; Mayorga-Martinez, Carmen C; Guan, Jianguo; Pumera, Martin (Small (Weinheim an der Bergstrasse, Germany), 2020)
Photocatalytic micromotors are light-induced, chemically powered micromachines based on photocatalytic materials, activated by light illumination, and have redox reactions with environmental solutions to produce chemical gradients and bubbles that propel the micromachines through self-diffusiophoresis, self-electrophoresis, and bubble recoil. Due to the fact that excitation light relates largely to the bandgaps of selected materials, the development of photocatalytic micromotors has experienced an evolution from ultraviolet-light-activated to visible-light-activated and potentially biocompatible systems. Furthermore, due to the strong redox capacity and physical effects caused by the products or product gradients, photocatalytic micromotors have applications in environmental remediation, micropumps, reversible assembly, transportation, and biomimicry.
Keywords: mikrotechnologie; Photochemical Processes; light-activated systems; ultrafialové záření; Ultraviolet Rays; Microtechnology; regenerace a remediace životního prostředí; Biomimetic Materials; Light; photocatalytic micromotors; Environmental Restoration and Remediation; product gradient; fotochemické procesy; biomimetické materiály; světlo